Strategy Construction and Practice Research of Embodied Teaching Integrated into Chemistry Experiment Teaching in High School - Jia, Miaomiao; Zhang, Min; Qu, Jinjie; Li, Huiya; Liao, Tianlu (Education Insights, 2026)
Under the guidance of core educational literacy, high school chemistry experiment teaching carries the critically important mission of cultivating students’ scientific inquiry abilities, practical skills, and innovative consciousness. However, there is a growing tendency of "separation" and "superficialization" in current experimental teaching methodologies. Frequently, students’ physical participation in laboratory settings is entirely disconnected from their underlying cognitive thinking and knowledge construction. Embodied teaching, an emerging pedagogical paradigm, emphasizes that human cognition is deeply rooted in bodily perception, sensorimotor interactions, and active physical experience. This framework provides a highly promising new perspective for comprehensive experimental teaching reform. Based on the foundational theory of embodied cognition, this study systematically analyzes the inherent pedagogical compatibility between embodied teaching principles and chemical experiment instruction. Furthermore, it critically examines the existing structural problems and limitations prevalent in current experimental teaching practices. To address these challenges, this research constructs a comprehensive five-dimensional strategy system designed to seamlessly integrate physical action with cognitive engagement. The implementation of this embodied teaching strategy demonstrates significant pedagogical benefits. It can effectively improve students’ hands-on experimental operation abilities, elevate their overall scientific thinking levels, and substantially boost their intrinsic learning interest. Ultimately, this study provides a highly practical and operational path for the systematic reform of high school chemistry experiment teaching, ensuring that students achieve a more holistic and deeply integrated scientific education.